NIAT WIRAUSAHA SOSIAL : PERAN PRIORITAS PENGALAMAN, SELF-EFIKASI WIRAUSAHA SOSIAL, DAN KEAMANAN FINANSIAL - Samsuria, Indranila Kustarini; Lukiastuti, Fitri (Magister Manajemen STIE Bank BPD Jateng, 2024)
The purpose of this study was to examine the relationship or influence of self-efficacy, social entrepreneurship, priority experience, and financial security on social entrepreneurship intentions. The research sample consisted of 100 MM STIE BPD Jateng students. The data were analyzed using a structural equation model to test the relationship between these variables, using PLS version 4. The results showed that social entrepreneurship intentions were significantly influenced by social entrepreneurship self-efficacy and priority experience with a p value <0.5. In addition, financial security also plays an important role in supporting social entrepreneurship intentions. Individuals with high levels of self-efficacy and priority practical experience tend to have strong intentions to enter social entrepreneurship. Financial security provides additional support by reducing the risks and uncertainties faced by prospective social entrepreneurs. This study provides important implications for the development of training programs and policies that support social entrepreneurship intentions. Increasing self-efficacy and providing opportunities for practical experience can encourage more individuals to engage in social entrepreneurship intentions. In addition, creating an environment that supports financial security will strengthen the success of social entrepreneurship intentions. Further research with strong theoretical support is recommended to explore and examine the dynamics of social entrepreneurship intentions and other factors that influence them